Estudio de prefactibilidad para la implementación de una planta procesadora de hojuela de papa deshidratada y papas fritas precocidas "ch'uñu foods" - Arribas López, Diego José (2016)
The proyect consist in identify and demonstrate the feasibility implementation and financial operation success of an dehydrated potato flake (DPF) and precooked fries (PF) provider plant. Due to shortage of DPF, because of the high global demand and growing demand on restaurants for PF. Which will be installed on the district of Ate in the city of Lima. All this using 100% Peruvian raw materials and local labor.